Assessment of the Water Quality Index for the Tigris River in Southeastern Iraq - Abdullah, Sajad; Ankush , Mujtaba A.; Ahmadifard, Nasrollah; Kangarloei , Behrouz A.; Miryaghoubzadeh, Mirhassan (Mesopotamian Journal of Marine Sciences, 2024)
The water quality in the southeast region of Iraq was evaluated in this study, which focused on the Tigris River one of Iraq’s primary water sources in Iraq. From August 2022 to July 2023, water samples were taken at four different stations on a monthly and seasonal basis between Al-Qurna and Al-Azayer cities. The study aims to estimate the quality of water in the Tigris River for potable water. Consumers will be able to use the information to identify various degrees of pollution. The eight parameters that were examined were as follows: water temperature, dissolved oxygen (DO), hydrogen ions (pH), turbidity, total hardness (TH), total dissolved solids (TDS), electrical conductivity (EC), and chloride (Cl-1). The four stations along the Tigris River showed different monthly fluctuations in the water quality index. The water quality index showed different monthly and seasonal fluctuations among the four study stations in the Tigris River. In station 1, the mean WQI value was 2.153 ± 0.557, indicating good water quality. However, the lowest WQI value (1.357) occurred in August, indicating poor water quality as the index decreased below 2.0. On the other hand, the highest value (2.800) in June and May indicated good water quality as the index of 2.0. Station 2 had a mean water quality index value of 1.915 ± 0.328, with values ranging from 1.326 in August to 2.150 in October. Station 3 reported a mean WQI of 1.793 ± 0.351, showing the lowest index (1.298) in August and the highest (2.100) in November, February, March, and May. At station 4, the water quality index varied from 1.393 in April to 2.100 in November, February, and March with a mean of 1.689 ± 0.358. Constructed on seasonal fluctuations with a general mean value of 1.869 ± 0.307, the Tigris River’s water quality can be considered poor quality. Winter and spring had the highest WQI values (2.151, 2.079), while summer and Autumn had the lowest WQI levels (1.483–1.761). Based on their average values, stations 2, 3, and 4 indicate poor water quality, considering the ideal value of the water quality index. An ANOVA analysis of the water quality index showed significant results (P < 0.05, F = 2.850, Sig = 0.048). These results suggest that the water in the entire river is unsuitable for potable water.